Critical care nursing made incredibly easy! (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
Covering various aspects of critical care and evidence-based nursing practice, this book offers coverage of moderate sedation and perianesthesia management, ACLS and code management, information on rapid response teams, and "Handle With Care" icon to identify concerns and actions relating to elderly, pediatric and bariatric patients